Physicochemical Properties of Breakfast Sausage Extended with Locust Bean Flour : 10.5958/2581-6616.2020.00010.9 - Koleoso, I. M.; Adeshola, A. T.; Olusola, O. O.; Akinsehinde , T. A. (Journal of Meat Science, 2021)
This study was carried out to assess the physicochemical and sensory properties of Breakfast Sausage (BS) prepared with varied levels of  African Locust Bean (ALB) flour. All flours were assessed for functional properties. Batches of BS were prepared using either ferment ed or unfermented ALB flour at inclusion levels of 2%, 3%, and 4% in replacement of soybean flour at 4% (control), in a completely  randomised design. Physicochemical and sensory parameters were determined using standard procedures. Data were analysed using  ANOVA. Functional properties of ALB flours were significantly different. Fermented ALB flour had highest (p
Keywords: African locust bean; Breakfast sausage; Functional properties; Physicochemical properties; Sensory evaluation